Mathematical literacy of high-school graduates - Bakštys, Albertas (Lietuvos matematikos rinkinys, 1999)
The paper deals with a test of mathematical literacy for high-school graduates; the method of estimating is present. The results of the test are compared with the points of school leaving certificate.